Femoral Nerve Palsy due to Anticoagulant Induced Retroperitoneal Hematoma - Orcun Gurbuz; Abdulkadir Ercan; Gencehan Kumtepe; İlker Hasan Karal; Yusuf Velioglu; Serdar Ener (Case Reports in Medicine)
A forty-one-year-old man who, sought evaluation for a sudden hip flexion contracture and groin pain with a history of mechanical mitral valve replacement, had been misdiagnosed and treated as having lumbar discopathy for two days. This patient finally was diagnosed with compressive femoral neuropathy due to warfarin-induced retroperitoneal hematoma and successfully managed nonoperatively. This case is reported in order to draw attention to this rare presentation.